KETERGANTUNGAN MASYARAKAT TERHADAP SUMBER DAYA HUTAN DI DESA MERAH ARAI KECAMATAN KAYAN HULU KABUPATEN SINTANG - Inde, Vebi Sola; Roslinda, Emi; Idham, M (Universitas Tanjungpura, 2020)
Forests function naturally as the foundation and coordinating life on the surface of the earth because in addition to producing wood, also produces non timber and environmental services, the results of non-timber forests in form of fruits, vegetables, spices, medicines and environmental services also such as accommodating water, holding floods, and filtering air pollution as well as a place for the life of animals and other creatures. This research aimed to find out how the peoples dependence in Merah Arai village to forest resources and research in also for describing public dependence on timber, non-timber and land-forest resources. The results of this research with public dependence on forest resources and as data for the community use the forest outcomes. The method of research that used is a survey method, while taking the respondence in the purposive sampling. Data analysis are done in a qualitative descriptive. The results showed that the community relies heavily on forest resources so that the dependency of society consists of the first three groups of timber forest use for construction, sampan and firewood. Utilization both products of non-timber forest in direct consumption such as fruits, some are in consumption after cooking such as vegetables, spices, and animals, there are also in the way of medicines. The third is the land is use for planting crops such as farming, paddy field, and gardening.Keyword : Community, dependence, Forest results.